2020
DOI: 10.3390/su12219190
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Its Relations to School Trajectory and Family Educational Capital in High Intellectual Ability Adolescents

Abstract: The psychological well-being of adolescents depends on diverse contextual factors, in particular those relating to the educational and cultural capital of families. The study examined the relationships between psychological well-being of high-ability adolescents, family educational capital, and their school trajectory. The participants were 101 students from 1st year of a public high school in Morelos, Mexico, previously identify by their high intellectual ability. They completed an ad hoc form with informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
0
0
1
Order By: Relevance
“…Cultural capital can be passed on to the next generation through parents and is both a scarce resource and a reward [25]. Recent studies have shown that students' cultural capital absorption can be directly translated into academic skills [26], which in turn leads to academic achievement at school [27]. At the macro level, educational inequality is shaped by the unequal distribution of cultural capital [15].…”
Section: Cultural Capital and Academic Achievementmentioning
confidence: 99%
“…Cultural capital can be passed on to the next generation through parents and is both a scarce resource and a reward [25]. Recent studies have shown that students' cultural capital absorption can be directly translated into academic skills [26], which in turn leads to academic achievement at school [27]. At the macro level, educational inequality is shaped by the unequal distribution of cultural capital [15].…”
Section: Cultural Capital and Academic Achievementmentioning
confidence: 99%
“…Ante este panorama, se destaca la necesidad de investigaciones acerca de las aptitudes sobresalientes en el contexto nacional (Valadez, Meda & Zambrano, 2006;Castellanos, Pérez & Hernández, 2020).…”
unclassified